Spermatogenesis and spermiogenisis in the testes of local Iraqi breed cat (Felis catus): AL-Samarrae,N.S. , AL-Maliki,S.H. , Eman musa and AL-Saedi,F.A. - S., AL-Samarrae N. (The Iraqi Journal of Veterinary Medicine, 2012)
The seminiferous epithelium of the testes of cat consists of two groups of cells; Spermatogenic cells and Sertoli cells. The interstitial areas are filled with Leydic cells, blood and lymph vessels, and connective tissue. Germ cells in the Spermatogenic process of the testis of cat can be classified into ten steps, based on the pattern degree of nuclear chromatin condensation. Primary spermatogonia contain large spherical nuclei with mostly euchromatin. Spermatogonia proliferate to give rise to spermatogonia type –A; Intermediate or type-I spermatogonia, and spermatogonia type-B. Type–B spermatogonia yield primary spermatocyte at the end of mitosis. The primary spermatocyte is transformed into secondary spermatocyte during meiosis I. These cells are converted into spermatid during meiosis II. Metamorphosis of spermatids shows: Golgi step, Cap step, Acrosomal step, Maturation step.